Low voltage driven surface micro-flow by Joule heating. Issue 47 (6th June 2017) - Wang, H.; Wang, S. G.; Kan, J. J.; Deng, X. Y.; Wang, W. C.; Wu, M. H.; Lei, Y.
Abstract : We report a low voltage driven surface microfluidic system simply by Joule heating. Abstract : We report an electrically controlled micro-flow of liquid on Au-patterned glass surfaces with a driving voltage lower than 10 volts. The Joule heating produced by electrical current passing through the Au layer activates the selective wetting of liquids, performing complicated micro-flow control over pre-designed circuits. Transportation and serial dilution of the dye molecules in the liquid are further demonstrated.